Strengths and weakness of neuroscientific investigations of childhood poverty: future directions - Lipina, Sebastián J.; Segretin, M. Soledad (Frontiers in Human Neuroscience, 2015)
The neuroscientific study of child poverty is a topic that has only recently emerged. In comparison with previous reviews (e.g., Hackman et al., 2009, 2010; Lipina & Colombo, 2009; Lipina & Posner, 2012; Raizada & Kishiyama, 2010), our perspective synthesizes findings, and summarizes both conceptual and methodological contributions, as well as challenges that face current neuroscientific approaches to the study of childhood poverty. The aim of this effort is to identify target areas of study that could potentially help build a basic and applied research agenda for the coming years.